Impact of Biomass Burning on Air Quality in Temuco City, Chile - Felipe Reyes; Sofía Ahumada; Francisca Rojas; Pedro Oyola; Yeanice Vásquez; Claudio Aguilera; Andres Henriquez; Ernesto Gramsch; Choong-Min Kang; Sanna Saarikoski; Kimmo Teinilä; Minna Aurela; et al. (Aerosol and Air Quality Research)
Abstract Residential wood burning emits a complex mixture of particulate and gaseous compounds. In this article we show an in-depth chemical characterization of particulate matter evidencing the impact of biomass burning on the urban air quality in Greater Temuco, the capital city of the Araucanía Region, Chile. The measurements were carried out at two sites, Las Encinas and Padre Las Casas, in spring and winter. Extremely high fine particulate matter (PM2.5) concentrations (up to 700 µg m–3) were frequently observed at both stations in the wintertime, while in spring, PM2.5 concentrations were significantly lower (campaign-average 6.4 and 8.6 µg m–3 in Las Encinas and Padre Las Casas, respectively). Chemical composition of submicron PM was dominated by organics (average 87%) followed by inorganic ions (10–30%) and a minor contribution of black carbon (< 5%). In the wintertime, atmospheric levels of biomass burning tracers, such as levoglucosan, potassium and chloride, were elevated and their diurnal profiles showed a significant concentration increase in the evening. Diurnal profiles combined with the in-depth chemical analysis clearly indicated that in the wintertime local biomass burning was the main source of air pollutants in the region. Furthermore, in winter, most of the high concentration events correlated with the periods with high surface pressure, low temperature and low wind speed. These events matched with higher temperatures at high altitude than at the surface characterizing the typical profile of a vertical inversion that prevents the dilution of air pollutants.